Sternalis Muscle: An Unexpected Finding during Mastectomy. (2nd November 2015) - Sasmal, Prakash K.; Meher, Susanta; Mishra, Tushar S.; Deep, N.; Tripathy, Prabhas R.; Rath, Satyajit
Abstract : Sternalis muscle also called rectus sternalis, rectus thoracis, or episternalis is an anomalous muscle of the anterior chest wall with unknown anatomical function. It is regularly observed in lower animal but infrequently in humans. Presence of this muscle can create confusion with tumours of the anterior chest wall during routine mammography. Although less is known about its origin and innervations, knowledge about this muscle can have many clinical implications. A case of unilateral sternalis muscle detected during mastectomy, in a female with carcinoma of the right breast, is being reported with a brief review of the literature and highlighting its clinical significance.